COVID-19 and liver dysfunction: current ideas and new therapeutic strategies - E. A. Lyalyukova; I. V. Dolgalev; E. N. Chernysheva; I. V. Druk; G. M. Konovalova; A. V. Lyalуukov (Лечащий Врач)
The purpose of the review is to present an analysis of the literature data on the etiopathogenesis and therapy of liver diseases while Covid-19. Liver damage is common in patients with COVID-19, which can be caused by the direct cytopathic effect of the virus, an uncontrolled immune response, sepsis, or drug damage to the liver. Given the presence of ACE2 receptors in the liver, the liver is a potential target for SARS-CoV-2. Moreover, COVID-19 may exacerbate underlying chronic liver disease, leading to hepatic decompensation, acute liver failure, associated with higher mortality. Doctors should carefully assess the initial state of the liver, pay attention to changes in the course of underlying liver disease, and during treatment should intensify monitoring and evaluation of liver function in patients with severe disease. The physician should establish the causes of liver damage in combination with the pathophysiological changes caused by COVID-19 and based on active treatment of the underlying disease, prescribe treatment to protect the liver to reduce the degree of liver damage. Additional data are currently required to clarify the nature and extent of liver damage, and to determine approaches to therapy in patients with COVID-19.